Therapeutic potential of thioctic (alpha-lipoic) acid in patients with diabetes mellitus type 2 and metabolic associated fatty liver disease - Yu.F. Marchuk; V.V. Vivsiannyk; I.I. Alieksieieva; D.R. Andriychuk (Mìžnarodnij Endokrinologìčnij Žurnal, 2025)
Background. Diabetes mellitus type 2 (T2DM) and metabolic associated fatty liver disease (MAFLD) are common metabolic diseases that are often accompanied by obesity, dyslipidemia and hypertension. An integrated approach to the treatment of these conditions is a challenge for modern medicine, which requires the development of effective and safe therapeutic strategies. The purpose was to study the effectiveness of thioctic (alpha-lipoic) acid at a dose of 600 mg/day in patients with type 2 diabetes mellitus and metabolic associated fatty liver disease against the background of comorbid metabolic disorders. Materials and methods. The study included 112 patients with T2DM and MAFLD aged 40 to 65 years who received thioctic (alpha-lipoic) acid at a dose of 600 mg/day for 12 weeks as part of comprehensive therapy. Glycemic control indicators (glycated hemoglobin level, fasting plasma glucose), liver function (transaminase level), lipid profile (total cholesterol level, triglycerides, low density lipoproteins), as well as inflammatory markers (C-reactive protein, interleukin-6) were evaluated. Results. The pronounced effectiveness of thioctic (alpha-lipoic) acid as part of comprehensive therapy was demonstrated: 86 % of patients showed a significant improvement in glycemic control, 78 % — normalization of functional liver indicators, 72 % — a decrease in the level of inflammatory markers. In addition, patients experienced an improvement in the quality of life and general well-being, a decrease in fatigue symptoms. Thioctic acid also showed a high safety profile: adverse events were minor and transient. Conclusions. Thioctic (alpha-lipoic) acid is a promising therapeutic agent that provides a simultaneous effect on key links in the pathogenesis of metabolic diseases. Its use in patients with comorbid conditions allows for improvement of clinical and laboratory indicators, which confirms its important role in modern clinical practice.